Optimizing the Experience of Flow for Adults With Aphasia: A Focus on Environmental Factors. Issue 1 (January 2017) - Sather, Thomas W.; Howe, Tami; Nelson, Nickola Wolf; Lagerwey, Mary
Abstract : Flow has been described as positive experiences of intense concentration, distorted time passage, and a loss of self-consciousness that result from matching task difficulty to a person's skill level. It has been studied in many different populations and has been associated with a number of positive outcomes, including improved life satisfaction and well-being, enhancement of identity, and the development of skills. Although flow has been identified as being important for adults with aphasia, it had not been studied in this population until recently. In this article, the authors describe the concept of flow and explain why it is important for clinicians to consider when working with adults with aphasia. Next, the authors review the literature related to barriers and facilitators that influence the experience of flow for adults with aphasia and conclude by identifying clinical implications for optimizing the experience of flow in this population.